Implementation of the Tuberculosis (TB) Program Management at Bontonompo 1 Community Health Center, Gowa - Mutmainnah Latief; Hardi, Hardi (Jurnal EduHealth, 2025)
Tuberculosis (TB) remains a major public health problem in Indonesia, with the number of cases continuing to rise, including in Gowa District. Community Health Centers (Puskesmas) play a strategic role in case detection, treatment, and monitoring of TB patients. This study aims to evaluate the implementation of TB program management at Bontonompo 1 Community Health Center, Gowa, based on the management functions: planning, organizing, implementing, and controlling. The research used a descriptive qualitative approach. Data were collected through observations, in-depth interviews with four informants (the Head of the Community Health Center, TB program officer, TB cadre, and TB patient), as well as documentation in the form of case reports, health profiles, and activity photos. The results showed that TB program planning was carried out in a structured manner through the Health Planning Meeting (Musrenbangkes) and evaluation of the previous year’s achievements. Strategies implemented included community education, early screening, close contact examination, and involvement of health cadres. Internal organization at the Community Health Center was well-structured with clear task distribution among program officers, laboratories, and cadres, although cross-sectoral coordination still needs to be strengthened. Program implementation followed national guidelines using DOTS and TOSS TB strategies, covering patient counseling, cadre assistance, and community education. The main challenges included low patient awareness, social stigma, and limited educational media. Program control was conducted through monthly patient monitoring, internal evaluation, and routine recording, although there were obstacles such as delays in reporting and cross-sector monitoring. In conclusion, the implementation of TB program management at Bontonompo 1 Community Health Center has been in line with national guidelines, but still faces challenges in organization and control.